Main causes and diagnostic evaluation in patients with primary complaint of olfactory disturbances - Fornazieri,Marco Aurélio (2014)
INTRODUCTION: Establishing a diagnosis in patients with olfactory disturbances has always been challenging for physicians.One reason for this is the rarity of some of the diseases that affect this sense, such as Kallmann's syndrome and post-viral olfactory loss. OBJECTIVE: To identify the major causes of olfactory disturbances and to describe the diagnostic evaluation in outpatients attended to at an ambulatory clinic specialized in olfaction disorders. METHODS: A retrospective analysis was performed in outpatients with primary olfactory complaint attended to between June 1, 2011 and September 30, 2013 in a center specialized in olfactory disorders. Patient history, nasofibroscopy, and the University of Pennsylvania Smell Identification Test (UPSIT) comprised the examination. RESULTS: Sixty-two patients were evaluated. The major causes were chronic rhinosinusitis (31%); rhinitis, primarily the allergic type (19%); post-viral olfactory loss (13%); and post-traumatic loss (8%). UPSIT scores were statistically different among different etiologies (p = 0.01). CONCLUSIONS: The major diagnoses that should be part of the physician assessment when a patient complains of olfactory disturbance are chronic rhinosinusitis with and without polyps, allergic rhinitis, post-viral olfactory loss, and post-traumatic loss.